Pemberdayaan Kesehatan Masyarakat Melalui Seminar Pencegahan Stunting di Desa Sei Merah Kabupaten Deli Serdang - Tri Niswati Utami; Azizah Mudrikah; Elma Fadilah; Lia Purnama Sari; M. Rifky Akbar; Rindi Safira (Jurnal Pengabdian UNDIKMA, 2022)
This community service activity aims to provide public health education regarding the prevention of stunting. Counseling in the form of seminars was used in this service. This service targeted the mothers in the village of Sei Merah, Deli Serdang Regency. The evaluation instrument for this activity used a questionnaire and interviews, which were then analyzed descriptively. The results of this service indicated that pregnant women's level of understanding of nutrition was still low because they had never followed counseling guidance. However, after this service seminar was conducted, there was a change in increasing the understanding of mothers regarding stunting prevention, namely by steps of (1) fulfilling nutrition during pregnancy, (2) fulfilling child nutrition optimally, (3) practicing proper hygiene, (4) overcoming children who have difficulty eating, and (5) consultation with the health care team.